DEMOKRASI SEBAGAI LANDASAN PEMBENTUKAN UNDANG-UNDANG DALAM PEMBAHARUAN HUKUM NASIONAL DI INDONESIA - Wulansari, Fadillah (HUNILA : Jurnal Ilmu Hukum dan Integrasi Peradilan, 2025)
The study aims to analyse the role of democracy as a base for the establishment of laws in the national legal reform in Indonesia. Democracy as a base principle of the rule of law guarantees the involvement of the people in the legislative process which produces laws that reflect the aspirations and needs of the community. The research method used is normative legal research with a legislative, conceptual, and historical approach. The data obtained from laws and regulations, legal literature, and expert opinions which are analysed descriptively-annalistically. The results of the study indicate that the application of democratic principles in the formation of laws which the main key to realizing laws that responsive and adaptive to social and political changes in Indonesia. Therefore, national legal reform must prioritize democratic principles that the legislative process is transparent, participatory, and accountable.